Sclerosing Angiomatoid Nodular Transformation of the Spleen: Radiological Findings and Radiological-pathological Correlation - Wu, Qingyang; Wang, Mingliang; Zhou, Ming; Feimiao; Ni, Jianming; Yin, Qihua (Current Medical Imaging, 2024)
IntroductionThe objective of this study was to describe the CT and MRI features of sclerosing angiomatoid nodular transformation (SANT) of the spleen with pathologic correlation.Materials and MethodsTen patients with surgically resected and pathologically confirmed SANTs were included. Clinical history was reviewed, and gross pathologic, histologic, and immunohistochemical findings were recorded. CT and MRI examinations were evaluated by two radiologists.ResultsPatients included seven men and three women, with a mean age of 42.9±16.7 years. Pathologic features of SANTs involved multiple angiomatous nodules in a radiating pattern with a central stellate fibrous scar and evidence of hemosiderin deposition. 9 cases showed a lobulated demarcated margin, 8 cases a slight hypoattenuating, 1 isoattenuating, and 1 case with two lesions demonstrated a slight hyperattenuating margin, respectively. Multiple scattered punctate calcifications were involved in 2 cases. 5 cases manifested hypointensity on in-phase imaging, 1 iso-intensity, and 4 iso-hypointensity on out-of-phase imaging. Progressive and centripetal enhancement were exhibited in 10 cases, spoke-wheel pattern in 3 cases, and nodular enhancement in 4 cases, respectively. The central fibrous scar was identified in 8 cases during delayed enhancement.ConclusionCharacteristics of SANTs on CT/MRI reflected the underlying pathology. Hypointensity on DWI and T2WI, and change of signal on T1 chemical-shift imaging were found to be due to hemosiderin deposition and fibrous tissue. Typical feature was a solitary, round, lobulated mass with a fibrous scar. Progressive and centripetal enhancement, spoke-wheel pattern, nodular enhancement, and delayed enhancement of central fibrous scar were observed.
Keywords: CT